(untitled) (Journal of University of Babylon for Engineering Sciences, 2021)
Course aggregate is the main constituent of Hot Mix Asphalt (HMA) in terms of percentage and load carrying mechanism. Practically, crush aggregate is extensively utilized in production of HMA because of its rough shape form that offers high interlocking, consequently, brings high resistance to traffic loads exposed from moving vehicles. The use of round aggregate in paving is not allowed by highway agencies, especially for surface layers, because of its smooth surface that does not give the required engineering properties. Thus, the coating process is suggested to rough the surface of round aggregate by using different materials to increase the strength for resisting the traffic load. In this research work, the coating process was introduced by using cement mortar comprising waste and natural materials, namely the glass waste particles and the natural sand. Low energy curing process is also used to minimize cost and time for curing of coated aggregates. Results of this research attempt showed that there is a significant improvement in the engineering and durability properties of HMA comprising coated round aggregate. Moreover, microwave treatment offers an alternative to relatively long time traditional curing. So, this can be reflected on minimizing the overall cost of construction of different pavement layers and the environmental impact come from crushing aggregate and use of natural materials can be reduced.